Neonatal compartment syndrome - Martin, B (Ann R Coll Surg Engl, 2016)
A term neonate was born with a grossly swollen and discoloured left hand and forearm. He was transferred from the local hospital to the plastic surgical unit, where a diagnosis of compartment syndrome was made and he underwent emergency forearm fasciotomies at six hours of age. Following serial debridements of necrotic tissue, he underwent split-thickness skin grafting of the resultant defects of his forearm, hand and digits. At the clinic follow-up appointment two months after the procedure, he was found to have developed severe flexion contractures despite regular outpatient hand therapy and splintage. He has had further reconstruction with contracture release, use of artificial dermal matrix, and K-wire fixation of the thumb and wrist. Despite this, the long term outcome is likely to be an arm with poor function. The key learning point from this case is that despite prompt transfer, diagnosis and appropriate surgical management, the outcome for neonatal compartment syndrome may still be poor.